2023
DOI: 10.1097/hc9.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health lifestyle intervention program leads to clinically significant loss of body weight in patients with NASH

Abstract: Background & Aims: Lifestyle intervention remains the foundation of clinical care for patients with NASH; however, most patients are unsuccessful in enacting sustained behavioral change. There remains a clear unmet need to develop lifestyle intervention programs to support weight loss. Mobile health (mHealth) programs offer promise to address this need, yet their efficacy remains unexplored. Approach & Results: We conducted a 16-week randomized controlled clinical trial inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Additionally, Duarte-Rojo et al [34] tested a smartphone application (EL-FIT, Exercise and Liver FITness) on inpatients with end-stage liver disease. Through interaction with all app features (videos, perceived exertion, and gamification/motivational features), the patients improved their physical performance by 35%, and similar results were described by Stine et al [35].…”
Section: Improving Physical Performance and Quality Of Lifesupporting
confidence: 83%
“…Additionally, Duarte-Rojo et al [34] tested a smartphone application (EL-FIT, Exercise and Liver FITness) on inpatients with end-stage liver disease. Through interaction with all app features (videos, perceived exertion, and gamification/motivational features), the patients improved their physical performance by 35%, and similar results were described by Stine et al [35].…”
Section: Improving Physical Performance and Quality Of Lifesupporting
confidence: 83%
“…The characteristics of the included studies were presented in Table 1 , supplemented with additional information. Predominantly, the studies were conducted in the USA [ 26 , 29 , 30 ], followed by Portugal [ 27 ] and Singapore [ 31 ]. Three out of the five studies, namely Lim et al, Policarpo et al, and Stine et al, were randomized controlled trials (RCTs) conducted at a single center within outpatient hospital and clinic settings.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the five included studies, three were included in the meta-analysis, while two studies were conducted with single-arm designs. Three studies (Lim et al, Policarpo et al, Stine et al) reported outcomes regarding BW and BMI [ 26 , 31 ]. However, one study (Policarpo et al) did not provide the standard deviation outcomes for alanine aminotransferase (ALT) and aspartate aminotransferase (AST) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stine et al 5 conducted a 16-week randomized controlled trial, including 20 patients with metabolic dysfunction–associated steatohepatitis (either liver biopsy evidence of metabolic dysfunction–associated steatohepatitis or an ultrasound, CT, or MRI study showing hepatic steatosis and one of the following: Fibrosis-4 Index ≥1.45 or vibration-controlled transient elastography measurement of liver stiffness >8.2 kPA or FibroScan-AST score >0.35) by using Noom app or 20 controls with the standard of care. Noom is a self-management app that guides calorie consumption, exercise, and stress relief.…”
Section: The Mobile App Era Maturesmentioning
confidence: 99%
“…These studies reveal the future of apps—point-of-care, just-in-time behavioral interventions that can be customized to the patient’s needs, maximizing effectiveness through digital phenotyping. 3 , 5 , 6 Pilot studies should now give way to larger, multicenter evaluations designed for generalizable effects. Randomization, thoughtful control arms, and enrollment of sufficient power to detect meaningful effects are needed.…”
Section: The Path Forwardmentioning
confidence: 99%